Zeitschrift für Pädagogik und Theologie (De Gruyter, 2016)
Founded in 1949 as Der Evangelische Erzieher, the ZPT is a leading international journal for the entire field of religious education. It introduces current research topics, provides information about new developments and publications, launches discussions, and offers innovative stimulus for the practice of religious education in schools and communities.